2019
DOI: 10.30521/jes.613724
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative simulation on the grounding grid system of a wind turbine with FEA software

Abstract: The mathematical models proposed in the literature are used to determine the grounding resistance value for electrical installations. These models are mathematical expressions that change according to grounding type and the mechanical properties of the grounding system elements. Besides, the inclusion of nonlinear terms is another important issue in the modeling studies. For the modeling of nonlinear systems and the analysis of the faults that may occur, the finite element analysis (FEA) approach provides real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…In the analysis settings stage, simulation conditions are determined for solution setup. According to the data obtained as a result of the analysis, reports such as numerical values, 2D/3D graphics and electromagnetic field drawings are obtained [17][18][19]. [17][18][19].…”
Section: Electromagnetic Modeling With Fea Softwarementioning
confidence: 99%
See 2 more Smart Citations
“…In the analysis settings stage, simulation conditions are determined for solution setup. According to the data obtained as a result of the analysis, reports such as numerical values, 2D/3D graphics and electromagnetic field drawings are obtained [17][18][19]. [17][18][19].…”
Section: Electromagnetic Modeling With Fea Softwarementioning
confidence: 99%
“…One of the software using FEA is Maxwell 2D/3D of ANSYS. Thus, the electromagnetic analysis can be performed during the development of permanent magnet alternators [15][16][17][18][19][20][21][22][23]. Before the prototype stage, the simulation studies with the electromagnetic analysis Maxwell software revealed that more realistic modeling was provided and the validity of the data obtained.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Today, electrical energy, as an indispensable type of energy, is vital in daily life, and possibly electrical and insulation faults that may occur during the use of electrical energy can pose a danger to the life of living things. Therefore, various protection measures such as grounding, insulation, and the use of low voltage must be taken to protect the life of living things and the system in electrical installations [1]. Grounding systems, an extremely safe protection measure, are the critical components of the protection system against lightning and fault currents of facilities, substations, transmission, and distribution lines in general electrical installations.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there are different methods for analyzing energy data from wind energy sources and parameter estimation. It is desirable that the error rate is at the lowest values in parameter estimation operations, and in recent years, the most accurate and fastest data processing can be achieved with hardware and software developments in computer technology [15,16].…”
Section: Introductionmentioning
confidence: 99%